2020
DOI: 10.1186/s12887-020-02078-w
|View full text |Cite
|
Sign up to set email alerts
|

Patient and family experience with chronic transfusion therapy for sickle cell disease: A qualitative study

Abstract: Background: There is a limited understanding of the patient and family experience of Chronic Transfusion Therapy (CTT) for prevention of complications of Sickle Cell Disease (SCD). We sought to understand patient and family experience with CTT using qualitative methods. Methods: Fifteen parents of children < 18 years old and nine children 12-18 years old with SCD who were receiving CTT for > 1 year were interviewed using a semi-structured interview format, and interviews were analyzed using open coding methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 32 publications
0
13
0
2
Order By: Relevance
“…Caregivers described fear of initiating CRCT due to concerns for infection and fear of medical events and reactions during transfusions while providers specifically described concerns for alloimmunization and iron overload. Previous studies with caregivers of children undergoing CRCT similarly found that logistical challenges, venous access, and fear and worry about CRCT were predominant negative themes, in addition to chelation therapy (Boateng et al, 2013; Hawkins et al, 2020). Chelation therapy was not noted as a barrier in the current study by caregiver participants (even among those with extensive CRCT experience).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Caregivers described fear of initiating CRCT due to concerns for infection and fear of medical events and reactions during transfusions while providers specifically described concerns for alloimmunization and iron overload. Previous studies with caregivers of children undergoing CRCT similarly found that logistical challenges, venous access, and fear and worry about CRCT were predominant negative themes, in addition to chelation therapy (Boateng et al, 2013; Hawkins et al, 2020). Chelation therapy was not noted as a barrier in the current study by caregiver participants (even among those with extensive CRCT experience).…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies have noted the importance of improving health literacy by providing accurate, disease-specific education about CRCT. In particular, information about likely complications and the role of families in the potential management of complications, such as alloimmunization or iron overload, is particularly important (Hawkins et al, 2020; Yee et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Raising a child with SCD is associated with a myriad of psychological stressors for primary caregivers 27 . Families experience stress from the burden of SCD treatments, such as CTT, regular clinic visits, and the financial hardship from missed workdays 27,28 . Taking care of their child through the pain crises and other severe SCD‐related complications may cause the greatest distress for primary caregivers 27 .…”
Section: Discussionmentioning
confidence: 99%
“… 27 Families experience stress from the burden of SCD treatments, such as CTT, regular clinic visits, and the financial hardship from missed workdays. 27 , 28 Taking care of their child through the pain crises and other severe SCD-related complications may cause the greatest distress for primary caregivers. 27 Primary caregivers cope in a variety of ways, such as joining support groups as well as engaging in health information–seeking behavior (HISB).…”
Section: Discussionmentioning
confidence: 99%
“… 37 Creary et al conducted a semi-structured interview of caregivers’ of the patients who were offered HU treatment, including those who agreed and those who refused HU, to understand their preferences regarding HU. 38 Caregivers identified the drug’s side effect profile, especially when HU is perceived as a chemotherapy drug, the uncertainty in disease progression, and inability to perceive the severity of SCD in their child as factors swaying them away from the medicine. They also found that even caregivers who chose HU for their children reported being fearful about initiating it.…”
Section: Qualitative Studiesmentioning
confidence: 99%